MENINGKATKAN PENGENALAN SAINS MENGGUNAKAN METODE KARYA WISATA PADA ANAK USIA 4-5 TAHUN DI PAUD AL-HIDAYAH KUBU RAYA - Selvianita, Selvianita; Purwanti, Purwanti; Ali, Muhamad (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe introduction of science has not been so applied, so that causing children to have less scientific ability, the purpose of this study is to improve the introduction of science using the method of tourism. The problem of this research is "How to improve the introduction of science using the method of tourism in children aged 4-5 years in Paud Al-Hidayah Kubu Raya". The research method that will be used in this research is classroom action research. The research subjects were 25 children. Based on the results of the actions taken, it can be stated that: 1) the planning that has been carried out has increased at each meeting, so that in the second cycle the fourth meeting was categorized as "good". 2) the implementation has been carried out at each meeting continues to increase starting from the first cycle with the category "enough", up to the second cycle with the category "good", 3) Increasing science introduction learning using the field trip method in each cycle has increased, this is evidenced in Cycle I criteria developed according to expectations with an average percentage reaching 32%, then in cycle II the average percentage developed according to expectations increased to 46%, and criteria developed very well appeared with an average percentage of 74%.Â Keyword: The introduction of science, The method of TourismAbstractThe introduction of science has not been so applied, so that causing children to have less scientific ability, the purpose of this study is to improve the introduction of science using the method of tourism. The problem of this research is "How to improve the introduction of science using the method of tourism in children aged 4-5 years in Paud Al-Hidayah Kubu Raya". The research method that will be used in this research is classroom action research. The research subjects were 25 children. Based on the results of the actions taken, it can be stated that: 1) the planning that has been carried out has increased at each meeting, so that in the second cycle the fourth meeting was categorized as "good". 2) the implementation has been carried out at each meeting continues to increase starting from the first cycle with the category "enough", up to the second cycle with the category "good", 3) Increasing science introduction learning using the field trip method in each cycle has increased, this is evidenced in Cycle I criteria developed according to expectations with an average percentage reaching 32%, then in cycle II the average percentage developed according to expectations increased to 46%, and criteria developed very well appeared with an average percentage of 74%.Â Keyword: The introduction of science, The method of Tourism